CHARACTERISTIC OF AUDITOR IMPACT TO AUDIT DELAY IN COMPANY LISTED IN BURSA EFEK INDONESIA - Santi Yopie (Management Department, Faculty of Economics and Business, Universitas Jambi, 2020)
The purpose of this study is to determine the characteristic auditor impact to audit delay. In this study the characteristic auditor is using audit committee size, audit committee meeting and audit committee expertise. The sample of this study is the companies which listed in Bursa Efek Indonesia and publish the annual report and audited report for the period of 2015-2019. Researchers used purposive sampling method, in which the research sample was not taken randomly but was based on aspects of consideration that were in accordance with the research objectives. The use of the purposive sampling method in this study was carried out by selecting companies which published annual report and audited financial report during the period year of 2015 to 2019. The research data were analyzed through multiple regression analysis using Eviews.The result of study showed that audit committee size and audit committee expertise has no significant effect to audit delay. The audit committee meeting has significant effect to audit delay. The contribution of this study is exploration the causes of audit delay for giving companies aware and prevent any audit delay which can cause costly penalty